Análise contra o conceito de trauma cultural: ou como aprendi a amar o sofrimento dos outros sem ajuda da psicoterapia - Wulf Kansteiner; Harald Weilnböck (e-cadernos ces)
The essay delivers a critique of the state of cultural trauma studies at the beginning of the 21st century. At that point in time, a few very influential texts, especially the publications of Cathy Caruth, helped establish a fairly homogenously structured interdisciplinary terrain that celebrated cultural trauma as a welcome disruption of existing cultural hegemonies and master narratives. Delivered from a deconstructive point of view, the cultural trauma discourse deployed clinical concepts of trauma but displayed no interest in the experiences and treatment of actual trauma victims. Moreover, the cultural trauma discourse emphasized the role of the media in the perpetuation of cultural trauma but failed to tap into existing media research thus mistakenly conflating mass media representations of violence with experiences of collective trauma. As a result of insufficient interdisciplinary curiosity and conceptual self-reflexivity, the cultural trauma discourse displayed troublesome anti-narrative and anti-empirical reflexes praising conventional, text-centered artistic and philosophical practices as sites of authentic aesthetic resistance against an allegedly repressive intellectual status quo.